Relationship Between Student Characteristics and Handwashing Habit with Worm Disease Incidence in Islamic Boarding School Blitar District - Aida Erna M; J Mukono (Universitas Airlangga, 2015)
Abstract: Worm disease incidence in islamic boarding school can be influenced by student characteristics and handwashing habit. Student characteristics were cocidered into age and lived period in islamic boarding school. Hand washing were seen from handwashing habit before ate and after defecation. Purpose of this study was to analyze relationship between student characteristics and handwashing habit with worm disease incidence in islamic boarding school. This study was observational analytic study with cross sectional design. Student characteristics and handwashing habit data were obtained questionnaires by 71 students. Worm disease incidence was known from laboratory testing of student feces. Worm disease incidence in islamic boarding school were 2.8% with worm species were Enterobius vermicularis and Hookworm. Results of data collection were analyzed using Chi Square test with value of α = 0.05. Student characteristics showed most student was 16 years old and live in boarding school for 1 year. Hand washing habit student islamoc boarding school before eating was bad and after defecation was good. There was a relationship between live period in islamic boarding school (p = 0.016), handwashing habit before eating (p = 0.008) and after defecation (p = 0.018) with worm disease incidence. There was no relationship between age and worm disease incidence (p = 0.205). Student islamic boarding school should improve handwashing habit before eating and after defecation used soap and running water.Keywords: student islamic boarding school characteristics, handwashing habit, worm disease, islamic boarding school